Analisis Strategi Promotion Mix (Advertising, sales promotion, personal selling, Public Relation) Pada Usaha Kecil Menengah (UKM) â€œBatagor Sarasa Bandungâ€ - Rd. Dewi Puspasari (SINTESA, 2022)
Promotion is one of the factors that determine the success of a marketing program, even if it is a quality product, if consumers have never known it and have not heard of it, they are not sure that the product will be useful for the consumer, so they will never buy it. In essence, promotion is a form of marketing communication. Marketing communication is a marketing activity that seeks to disseminate information, persuade, or influence and remind target consumers of their products so that these consumers are willing to buy the products they sell or offer. According to Kotler (2016) explaining that the promotion mix is the best combination of strategies from promotional elements used to achieve company goals. Where these elements are tools of the company's marketing communicators in communicating with customers. This study aims to determine the promotion mix or promotion mix applied to Small and Medium Enterprises (UKM) Batagor Sarasa Bandung. This research method uses descriptive qualitative research methods. Data collection was done by interview, observation, and documentation. Sampling was done by means of purposive sampling. The research data were analyzed using data analysis techniques according to Miles and Huberman with the stages of data collection, data reduction, data presentation and data conclusion drawing. The results showed that the Batagor Sarasa Small and Medium Enterprises (SMEs) had implemented a promotional mix using advertising, sales promotion, personal selling, direct marketing and public relations. This is evidenced by the advertising used by Batagor Sarasa Bandung Small and Medium Enterprises (SMEs) using brochures, banners, banners and social media then Batagor Sarasa Bandung SMEs also implement sales promotion using vouchers and discounts, as well as cashback in addition, UKM Batagor Sarasa Bandung conducts product publicity to inform consumers or the public about products, one of which is by participating in the bazaars held. Furthermore, efforts to improve the implementation of the promotion mix of Batagor Sarasa Small and Medium Enterprises (SMEs) conduct advertising by updating the content of the product and then on personal selling by using the suggestion box, then with sales promotion, doing vouchers and discounts when making purchases online. in market places such as Tokopedia, Shopee Food, Go Food, Grab Food and finally publicity by understanding consumer needs and complaints and participating in bazaars.